The Impact of Special Exercises for the Development of a Deep Sense of Block Skill Accuracy in Volleyball for Player's Focal Youth - Bassem Hassan Ghazi (Journal of Global Pharma Technology, 2018)
The Aim of ResearchPreparation of special exercises to develop the deep sense and the accuracy of block in the volleyball for focal young players.Learn the effect of special exercises in the development of deep sense and the accuracy of the block of the volleyball of focal young players.HypothesisSpecial exercises have a significant effect on the development of the deep sense and the accuracy of block of the volleyball of the focal young players.As for the research methodology, the researcher chose the experimental method as the appropriate method to solve the problem of research in the design of a single group with the pre and posttests.The sample of the research was chosen from the research community represented by the young players (17-19) years for the Kufa and Al Rawdatain 2016-2017 clubs. The number of players was chosen from them. The number of players was 4 players in each team. The total number of players was 8.The Researcher ConcludedAn evolution in the deep sense of the young players for the movement of the parties to the experimental group.Exercises for deep sense and accuracy contributed to increase the accuracy of the wall of the ball of the volleyball players.The various special exercises developed by the researcher contributed to the development of deep sense and accuracy of the wall barrier.The recommendations wereThe need to use special exercises in the development of deep sense and the accuracy of the wall of the block of the volleyball of young players.The need to develop a deep sense and accuracy of the skill of the wall of the young players to defeat the importance.The need to use exercises for the deep sense of other skills.Keywords: Special exercises, Deep sense, Block skill and focal youth.